Answer:
Step-by-step explanation:
S = 2WL + 2LH + 2WH
S - 2WH = 2WL + 2LH
S - 2WH = L(2W + 2H)
(S - 2WH) / (2W + 2H) = L <===
For this case we must factor the following equation:
It is observed that both terms contain the variable "d", so we can take it out as a common factor:
On the other hand, we look for the factors of 36 and 121:
36: 1,2,3,4,6,9,12,18,36
121: 1, 11,121
The greatest common factor between both numbers is 1.
Thus, the expression is factored as:
Thus, one of the roots of the polynomial is 0.
Answer:
B. (-4)(3)+(-4) 1/4
C. (3)(-4)x(3) 1/4
D. (3)(-4)+(3)(1/4)
Answer ASAP!
Answer:
the answer is c.
not 100% sure
Step-by-step explanation: